The impact of the demographic transition on poverty reduction in Central Asia - Kurbanova Muyassar (Proceedings of the European Union’s Contention in the Reshaping Global Economy, 2022)
Central Asian countries are experiencing a demographic transition due to the shrinking fertility and mortality rates and are at the stage of getting benefits from the demographic tailwinds with an increased working-age population share. This potential may convert the transition into economic growth and poverty reduction. Although all countries' economies grow, poverty reduction stagnated. The main question is whether this stagnation is due to an increase in the working-age population and whether the region can utilize this benefit to reduce poverty through accumulating human recourses. This paper analyzes the main channels that impact demographic change with the human capital in the socio-economic situation and the poverty rate of Central Asian countries by using cross-section data from the period 2000 to 2019 using the fixed effects method. The results suggest that the share of working-age population, human capital, GDP per capita, and female labor force participation rate will reduce poverty in the region.